Program Televisi Indonesia: Menguatkan ataukah Melemahkan Pancasila? - Harmonis; Bono Setyo; Sinung Restendy (Program Studi Ilmu Komunikasi, 2023)
As the ideology and basic philosophy of the state, the values of Pancasila must be reflected in television broadcast programs in Indonesia as confirmed in articles 2 and 5 of Law No.32/2002. This research was conducted to analyze the content of broadcasting programs from the point of view of Pancasila values, and the efforts made by stakeholders in broadcasting, such as the Central Indonesian Broadcasting Commission (KPIP) in order to strengthen these values. Research using qualitative methods. Data was collected through documents and in-depth interviews. Informants were selected purposively. The results of the study show that among the many broadcast programs in Jakarta that carry out national broadcasts, there are still broadcast program contents that have not implemented Pancasila values, such as soap opera programs. The reason is due to the weak understanding of Pancasila values and the domination of ratings in the television industry in Indonesia. For this reason, various efforts are needed that can make broadcasters commit to implementing Pancasila values.